The Call To Holiness: The Effect Of Understanding Concept Of Second Coming At GPdI Rajawali’s Youth Surabaya - Nina Astrid Karina (Jurnal Didaskalia, 2020)
Holiness is the condition, means and purpose for all believers that distinguishes them as God's people. In contrast to the condition of the world which is increasingly immersed in sin, the holiness of the believer will continue to progress until it reaches perfection. Starting from believing until finally when Christ comes the second time. This research was conducted to prove that the understanding of the concept of the second coming of Christ affects the holiness of the GPdI Rajawali Surabaya’s youth. From the quantitative research that has been done, it is evident that understanding this concept has a positive effect in the moderate category.